Aktivitas Hipolipidemik dan Indeks Aterogenik yang Rendah Ekstrak Air Daun Tapak Dara pada Tikus Hiperkolesterolemia (HYPOLIPIDEMIC ACTIVITY AND LOW ATHEROGENIC INDEX OF AQUEOUS LEAF EXTRACTS OF CATHARANTHUS ROSEUS IN HYPERCHOLESTEROLEMIC RATS) - Suarsana, I Nyoman; Utama, Iwan Harjono; Kardena, I Made; Suartini, I Gusti Ayu Agung; Watiniasih, Ni Luh (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Catharanthus roseus is one plant recognized as medical potential which can decrease cholesterol. Thepresent study was carried out to evaluate the effect of aqueous leaf extracts of C. roseus on plasma lipidprofil levels in rats cholesterol rich diet and atherogenic index. This study was carried out on 15 SpraqueDawley male rats randomly distributed into five groups (n=3). Rats hypercholesterolemic wereadministrated cholesterol rich diet containing 1% (w/w). Normal control group with normal diet whitoutextracts (K1), positive control hypercholesterolemic group (K2) with cholesterol rich diet whitout extracts,and others three groups (K3-K5) were feed high cholesterol and 1 mL of aqueous leaf extracts of C. roseuswith a dose of 20% (w/v), 40% (w/v) and 80% (w/v) respectively, administered twice daily 1 mL orally.Treatment was given for 28 days. After treatment, the plasma lipids profile such cholesterol total, highdensity lipoprotein (HDL), low density lipoprotein (LDL), triglyceride (TGA) level were measured. Theresults showed that during the period of treatment with cholesterol rich diet have produced under condition hypercholesterolemic of rats with average cholesterol levels of 124.33 ± 4.04 mg/dL (K2 group). Treatmentwith extract dose of 80% showed the best results among the other doses in reducing levels of total cholesterol,triglycerides, LDL and raise HDL levels. Extract treatment dose of 80% up to four weeks resulted incholesterol total (79.33±3.51 mg/dL), TGA (72.33±6.65 mg/dL), HDL (55.00±3.60 mg/dL), and LDL(9.87±5.34mg/dL). In addition, value ratio of cholesterol:HDL was 1.4: 1 and atherogenic index value was0.44. These results suggest that extracts of leaf C. roseus optimum doses 80% (w/v) has hipolipidemicactivity in hypercholesterolemic rats and it has low atherogenic index value.
Keywords: hypolipidemic, atherogenic index, Chataranthus roseus, profile lipid